Exploring the Interaction of Cobalt Oxide Nanoparticles with Albumin, Leukemia Cancer Cells and Pathogenic Bacteria by Multispectroscopic, Docking, Cellular and Antibacterial Approaches - Arsalan, Niloofar (Int J Nanomedicine, 2020)
AIM: The interaction of NPs with biological systems may reveal useful details about their pharmacodynamic, anticancer and antibacterial effects. METHODS: Herein, the interaction of as-synthesized Co(3)O(4) NPs with HSA was explored by different kinds of fluorescence and CD spectroscopic methods, as well as molecular docking studies. Also, the anticancer effect of Co(3)O(4) NPs against leukemia K562 cells was investigated by MTT, LDH, caspase, real-time PCR, ROS, cell cycle, and apoptosis assays. Afterwards, the antibacterial effects of Co(3)O(4) NPs against three pathogenic bacteria were disclosed by antibacterial assays. RESULTS: Different characterization methods such as TEM, DLS, zeta potential and XRD studies proved that fabricated Co(3)O(4) NPs by sol-gel method have a diameter of around 50 nm, hydrodynamic radius of 177 nm with a charge distribution of −33.04 mV and a well-defined crystalline phase. Intrinsic, extrinsic, and synchronous fluorescence as well as CD studies, respectively, showed that the HSA undergoes some fluorescence quenching, minor conformational changes, microenvironmental changes as well as no structural changes in the secondary structure, after interaction with Co(3)O(4) NPs. Molecular docking results also verified that the spherical clusters with a dimension of 1.5 nm exhibit the most binding energy with HSA molecules. Anticancer assays demonstrated that Co(3)O(4) NPs can selectively lead to the reduction of K562 cell viability through the cell membrane damage, activation of caspase-9, -8 and -3, elevation of Bax/Bcl-2 mRNA ratio, ROS production, cell cycle arrest, and apoptosis. Finally, antibacterial assays disclosed that Co(3)O(4) NPs can stimulate a promising antibacterial effect against pathogenic bacteria. CONCLUSION: In general, these observations can provide useful information for the early stages of nanomaterial applications in therapeutic platforms.